INFLUENCE OF POST-HARVEST PROCESSING METHODS ON CHEMICAL COMPOSITION, DRY MATTER AND ORGANIC MATTER DEGRADABILITY OF ACACIA (Acacia hockii) LEAF MEAL (FUDMA JOURNAL OF SCIENCES, 2020)
Three fistulated rams with average live weight of 20kg were used as replicates in a completely randomized design (CRD) to study the influence of post-harvest processing methods on chemical composition, In Sacco dry matter degradability (DMD) and organic matter degradability (OMD)  of three differently processed Acacia hockii leaf meal. The processed leaf meals (ensiled, T1; sundried, T2 and fresh, T3) were incubated in the rumen of the three rams (3, 6, 12, 24 and 48h incubation time). The processing significantly (p
Keywords: Degradability, Processing methods, Ram, Rumen and Acacia hockii